2015
DOI: 10.1111/acem.12625
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physician Perceptions of Medically Unnecessary Advanced Diagnostic Imaging

Abstract: Objectives: The objective was to determine emergency physician (EP) perceptions regarding 1) the extent to which they order medically unnecessary advanced diagnostic imaging, 2) factors that contribute to this behavior, and 3) proposed solutions for curbing this practice.Methods: As part of a larger study to engage physicians in the delivery of high-value health care, two multispecialty focus groups were conducted to explore the topic of decision-making around resource utilization, after which qualitative anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(160 citation statements)
references
References 69 publications
5
153
0
2
Order By: Relevance
“…20 While several studies have suggested that SDM may lower health care costs and usage, 4,5,7,8 others have questioned its ability to do so. 25 In either case, we believe that it would be inappropriate to promote SDM predominantly as a cost-saving measure, as the primary goal of SDM relates to its role in supporting the ethical obligation of physicians to ensure that patients have the opportunity to choose the care that is most suitable for them, when a reasonable choice exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 While several studies have suggested that SDM may lower health care costs and usage, 4,5,7,8 others have questioned its ability to do so. 25 In either case, we believe that it would be inappropriate to promote SDM predominantly as a cost-saving measure, as the primary goal of SDM relates to its role in supporting the ethical obligation of physicians to ensure that patients have the opportunity to choose the care that is most suitable for them, when a reasonable choice exists.…”
Section: Discussionmentioning
confidence: 99%
“…20 Briefly, this was a cross-sectional survey approved by our institutional review board. The final survey was administered to a nationally distributed, purposive sample of EPs recruited at four EM conferences (including Society for Academic Emergency Medicine and continuing medical education conferences) and 15 distinct ED group meetings.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Indeed, physicians are far more likely to order interventions that financially benefit them personally, [13][14][15][16][17] and acknowledge sometimes ordering medically unnecessary tests and treatments, because of malpractice concerns or the fear of being blamed if something goes wrong. 18,19 Cost-sharing is also patently unjust, as it hits hardest the pocketbooks of the poor and older adults. Although truly substantial cost-sharing would likely deter most everyone other than the very wealthy, this would be politically unfeasible; relatively limited cost-sharing, on the other hand, can be expected to primarily deter the poor, and older adults on a fixed income, from accessing health care.…”
Section: Paul Atkinsonmentioning
confidence: 99%
“…The frequency of head CT varies, as does the performance and resultant radiation dose estimations across ages [26][27][28][29]. In addition, there is variability in adherence to best practice clinical guidelines [30][31][32][33][34]. The issue of head CT and cancer risk is debated [35][36][37][38][39][40][41]; parental as well as emergency department providers' understanding of medical radiation exposure and cancer risk can vary [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%